Analytical Study of Performance and Emission Characteristics of a Palm Biodiesel Fuelled Engine using Response Surface Methodology - Teoh, Yew Heng; Balakrishnan Navaneetha, Krishnan; How, Heoy Geok; Shangeetha, Ganesan; Yu, Kok Hwa; Hishammudin Afifi, Huspi (Semarak Ilmu Publishing, 2020)
Alternative fuels are in the limelight due to depleting fossil fuel reserves and alarming environmental impact of pollution. Even though electric mobility is encouraged by the government to reduce the dependence on fossil fuel, lack of high energy density batteries still downplays the mass marketable scope of electric vehicles due to drivable range in which liquid fueled vehicles have the advantage. Response Surface Methodology (RSM), a statistical mathematic technique is utilized to analytically study the impacts of Palm Biodiesel (PBD) blended diesel fuel at enrichment ratio of 10%, 20%, and 40% on performance and emission characteristics of a multi cylinder compression ignition (CI) engine. The study concludes that engine torque and power improve with mild palm oil enrichment of 10% notably at low end speed of 2000 rpm. CO2 and CO emissions and smoke decline while higher O2 content present in PBD compared to pure Diesel gives rise to NOX emissions.